Circadian variation of lymphocyte subpopulations: a study with monoclonal antibodies. - Ritchie, A W (1983)
Use of monoclonal antibodies to identify subpopulations of circulating lymphocytes in healthy adults showed pronounced circadian variations in total T cells, the two major T cell subsets, and HLA-DR+ lymphocytes. When the results for the T cell subsets were expressed as a ratio (helper:suppressor) no significant rhythmic variation was observed. Lymphocytes bearing a surface antigen identified by the HNK-1 antibody (a population containing the natural killer and antibody dependent killer activity) did not show significant rhythmic variation. There was an inverse relation between plasma cortisol concentration and numbers of T and B cells. These observations have therapeutic implications and should be considered in the course of immunological monitoring.